Analisis Potensi pengembangan kebijakan industri pertahanan dengan pendekatan Total Quality Management (TQM) pada PT.PAL: Analisis Potensi pengembangan kebijakan industri pertahanan dengan pendekatan Total Quality Management (TQM) pada PT.PAL - andy ferdiyasto; Aries Sudiarso; IB Putra Jandhana; Fatmawati Fatmawati; Rudy AG Gultom (CV. AFDIFAL MAJU BERKAH, 2023)
This article discusses the analysis of potential defense industry policy development with the Total Quality Management (TQM) approach. The defense industry plays an important role in maintaining the security and sovereignty of a country. In the face of increasingly complex and dynamic security challenges, the product quality and competitiveness of the defense industry must be continuously improved. TQM has proven effective in improving performance and quality in various industrial sectors. This approach emphasizes continuous quality improvement and involves all members of the organization in process and product improvement. In the context of the defense industry, TQM is becoming increasingly relevant to achieve industrial independence and improve competitiveness in the global market. This research uses literature study, data analysis, and case studies of defense industries in several countries. This data is used to identify strengths, weaknesses, opportunities, and threats in developing the defense industry with a TQM approach. The results of this analysis are expected to contribute to policy makers and defense industry management in formulating strategies to improve the independence, efficiency and overall quality of the defense industry. By exploring the potential for developing defense industry policies with a TQM approach, the country can strengthen its defense capabilities, increase the contribution of the defense industry in supporting national security, and face the future with greater confidence and resilience. By exploring the potential of integrating the TQM approach into defense industry policies, this research strives to fortify a nation's defense capabilities. It also seeks to amplify the defense industry's role in bolstering national security. Consequently, this comprehensive analysis offers a blueprint for a future that promises increased self-assuredness and resilience, enabling the country to navigate evolving security challenges with confidence and adeptness.